EU fiscal rules: issues and lessons from political economy - Ludger Schuknecht (European Central Bank (ECB), 2004)
The paper analyses the EU fiscal rules from a political economy perspective and derives some policy lessons. Following a literature survey, the paper stresses the importance of appropriate incentives for rule compliance in an environment where national fiscal sovereignty precludes the option of centralised enforcement. In addition, the paper stresses the importance of clear and simple rules and in particular the 3% deficit limit in anchoring expectations of fiscal discipline and facilitating public and market monitoring of public finances. This, in turn, strengthens incentive for rule compliance. Moreover, the paper discusses the interests of the most important players in European fiscal rule formation and the importance of choosing the appropriate time for initiating a reform debate.
Keywords: D7; H3; H6; 330; deficits; fiscal rules; institutional reform; political economy; Stability and Growth Pact